The possible role of NLRP3 inflammasome in depression and myocardial infarction comorbidity - BAYSAK, ERENSU; YILDIRIM, ÇAĞAN; SAYAR, NURTEN; SAYAR, MUSTAFA KEMAL; ARICIOĞLU, FEYZA (My University, 2023)
It is well-established that cardiovascular disease and depression are highly comorbid. This study aimed to assess the possible role of the NOD-like receptor protein 3 (NLRP3) inflammasome pathway and the high-sensitivity C-reactive protein (hsCRP) in patients with incident myocardial infarction in the presence or absence of depression. Sixty-eight consecutive patients with incident ST-elevation myocardial infarction and twenty healthy subjects were included. The patients were assessed using the Structured Clinical Interview for DSM-5 Disorders—Clinician Version during their 1–4-day-long hospitalization and were divided into two groups: with and without comorbid depression. Blood samples for the determination of NLRP3, interleukin-18 (IL-18), interleukin-1β (IL-1β), and hsCRP levels were analyzed using ELISA. NLRP3, IL-1β, IL-18, and hsCRP levels were significantly higher in myocardial infarction patients compared to the healthy group (p = 0.02, p < 0.001, p < 0.001, and p < 0.001, respectively). No significant difference was found between the myocardial groups with and without depression. However, in the logistic regression analysis, the NLRP3 variable in myocardial infarction patients was found to have a significant contribution to the likelihood of depression (p = 0.015, OR = 1.72, and CI = 1.11–2.66). The likelihood of depression is associated with increasing NLRP3 levels in myocardial infarction patients. However, this potential role should be further explored in a larger sample.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Tıp (çeşitli); Medicine (miscellaneous); depression; hsCRP; myocardial infarction; NLRP3; NOD-like receptor protein 3